The Qur'an's Perspective on Poverty: A Comprehensive Analysis - Maraulang, Maraulang (Journal of Indonesian Islamic Studies, 2025)
Poverty is a persistent global challenge with multifaceted dimensions affecting societies worldwide. In Islamic teachings, the Qur'an provides comprehensive insights into poverty, addressing its economic aspects and moral and social implications. This study explores the Qur'an's perspectives on poverty, examining its relevance in modern socio-economic contexts and proposing strategies for effective poverty alleviation. Islamic teachings emphasize social justice, equality, and collective responsibility, which are crucial for understanding and addressing poverty. Concepts such as zakat (obligatory almsgiving), sadaqah (voluntary charity), and waqf (endowment) serve as foundational instruments for wealth redistribution and social cohesion. These teachings advocate for a society where the affluent support the less fortunate, fostering a more equitable distribution of resources. In contemporary society, poverty persists despite economic growth and development efforts. The Qur'anic principles offer holistic approaches to poverty that encompass spiritual, moral, and economic dimensions. These include empowering individuals through education and skills development, promoting economic self-reliance, and ensuring fair access to resources and opportunities for all members of society. This research employs a literature review methodology to explore Qur'anic insights on poverty, analyzing verses and interpretations from Islamic exegesis (tafsir) and scholarly works. It identifies key themes such as the obligation to give, the ethical considerations of wealth, and the role of community solidarity in poverty alleviation. The findings contribute to theoretical knowledge in Islamic studies and practical guidance for policymakers and social institutions seeking effective strategies to combat poverty. By integrating Qur'anic teachings into poverty alleviation strategies, this study proposes a framework for sustainable development that addresses the root causes of poverty while promoting social justice and collective well-being. Understanding and applying these teachings not only benefit Muslim communities but also offer valuable insights for global efforts to achieve inclusive and sustainable development goals